2018
DOI: 10.1177/0022034518762090
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Prognostic Value of Tissue-Based MicroRNA Expression in Oral Squamous Cell Carcinoma: A Systematic Review and Meta-analysis

Abstract: Oral squamous cell carcinoma (OSCC) is a common type of cancer characterized by a low survival rate, mostly due to local recurrence and metastasis. In view of the importance of predicting tumor behavior in the choice of treatment strategies for OSCC, several studies have attempted to investigate the prognostic value of tissue biomarkers, including microRNA (miRNA). The purpose of this study was to perform a systematic review and meta-analysis to evaluate the relationship between miRNA expression and survival o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 41 publications
1
62
0
5
Order By: Relevance
“…Since the EMT is highly associated with drug resistance (58), it is likely that the ZBTB7A-TRAIL-R2 axis may also attenuate EMTassociated drug resistance. Since disruptions of the miR-371-miR-373 cluster and the chromosome 19q13 locus are rather common in malignancies (4,6,8,10,(12)(13)(14), genome-wide studies should help with a more comprehensive understanding of how aberrations in the miR-372-ZBTB7A-TRAIL-R2 cascade affect oncogenicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the EMT is highly associated with drug resistance (58), it is likely that the ZBTB7A-TRAIL-R2 axis may also attenuate EMTassociated drug resistance. Since disruptions of the miR-371-miR-373 cluster and the chromosome 19q13 locus are rather common in malignancies (4,6,8,10,(12)(13)(14), genome-wide studies should help with a more comprehensive understanding of how aberrations in the miR-372-ZBTB7A-TRAIL-R2 cascade affect oncogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…miR-372/miR-373 were then found to be oncogenes that target LATS2, CD44 and various other differentiation regulators active in tumors (12,13). They are upregulated in malignancies and their upregulation of expression of miR-372/miR-373 has been found in HNSCC and miR-372 expression in tumors is a prognostic marker of OSCC (6,8,14). Serum miR-372 levels are potential diagnosis and prognosis biomarkers in neoplasms including HNSCC (4,15).…”
Section: Introductionmentioning
confidence: 99%
“…After integration into the RNA-induced silencing complex (RISC), the mature miRNA regulates the target gene mRNA expression [6]. Recently, meta-analyses have revealed that the upregulation of 9 miRNAs ( miR-21 , miR-455-5p , miR-155-5p , miR-372 , miR-373 , miR-29b , miR-1246 , miR-196a , and miR-181 ) and the downregulation of 7 miRNAs ( miR-204 , miR-101 , miR-32 , miR-20a , miR-16 , miR-17 , and miR-125b ) are strongly correlated with poor prognosis in OSCC patients [83]. Long noncoding RNA (lncRNA), a class of non-protein coding transcripts longer than 200 nucleotides, is also associated with gene expression and cancer progression [84].…”
Section: Novel Prognosticators Of Osccmentioning
confidence: 99%
“…A recent systematic review and meta-analysis has revealed that downregulation of miR-204 was correlated with poor prognosis in OSCC [69]. In other cancer types, it appears miR-204 also serves as a tumor suppressor.…”
Section: Microrna-204mentioning
confidence: 99%